Direct numerical simulation of viscoelastic-fluid-based nanofluid turbulent channel flow with heat transfer *Project supported by the National Natural Science Foundation of China (Grant No. 51276046), the Specialized Research Fund for the Doctoral Program of Higher Education of China (Grant No. 20112302110020), the China Postdoctoral Science Foundation (Grant No. 2014M561037), and the President Fund of University of Chinese Academy of Sciences, China (Grant No. Y3510213N00). (August 2015) - Yang, Juan-Cheng; Li, Feng-Chen; Cai, Wei-Hua; Zhang, Hong-Na; Yu, Bo
Abstract Our previous experimental studies have confirmed that viscoelastic-fluid-based nanofluid (VFBN) prepared by suspending nanoparticles in a viscoelastic base fluid (VBF, behaves drag reduction at turbulent flow state) can reduce turbulent flow resistance as compared with water and enhance heat transfer as compared with VBF. Direct numerical simulation (DNS) is performed in this study to explore the mechanisms of heat transfer enhancement (HTE) and flow drag reduction (DR) for the VFBN turbulent flow. The Giesekus model is used as the constitutive equation for VFBN. Our previously proposed thermal dispersion model is adopted to take into account the thermal dispersion effects of nanoparticles in the VFBN turbulent flow. The DNS results show similar behaviors for flow resistance and heat transfer to those obtained in our previous experiments. Detailed analyses are conducted for the turbulent velocity, temperature, and conformation fields obtained by DNSs for different fluid cases, and for the friction factor with viscous, turbulent, and elastic contributions and heat transfer rate with conductive, turbulent and thermal dispersion contributions of nanoparticles, respectively. The mechanisms of HTE and DR of VFBN turbulent flows are then discussed. Based on analogy theory, the ratios of Chilton–Colburn factor to friction factor for different fluid flow cases are investigated, which from another aspect show the significant enhancement in heat transfer performance for some cases of water-based nanofluid and VFBN turbulent flows.